Receptor-Targeted, Magneto-Mechanical Stimulation of Osteogenic Differentiation of Human Bone Marrow-Derived Mesenchymal Stem Cells - Hu, Bin (MDPI, 2013)
Mechanical cues are employed to promote stem cell differentiation and functional tissue formation in tissue engineering and regenerative medicine. We have developed a Magnetic Force Bioreactor (MFB) that delivers highly targeted local forces to cells at a pico-newton level, utilizing magnetic micro- and nano-particles to target cell surface receptors. In this study, we investigated the effects of magnetically targeting and actuating specific two mechanical-sensitive cell membrane receptors—platelet-derived growth factor receptor α (PDGFRα) and integrin ανβ3. It was found that a higher mineral-to-matrix ratio was obtained after three weeks of magneto-mechanical stimulation coupled with osteogenic medium culture by initially targeting PDGFRα compared with targeting integrin ανβ3 and non-treated controls. Moreover, different initiation sites caused a differentiated response profile when using a 2-day-lagged magneto-mechanical stimulation over culture periods of 7 and 12 days). However, both resulted in statistically higher osteogenic marker genes expression compared with immediate magneto-mechanical stimulation. These results provide insights into important parameters for designing appropriate protocols for ex vivo induced bone formation via magneto-mechanical actuation.